2020
DOI: 10.4103/tp.tp_62_19
|View full text |Cite
|
Sign up to set email alerts
|

Canine intestinal parasitic infections and soil contamination by Toxocara spp. in selected areas of Sri Lanka

Abstract: Introduction: Contaminated environment with canine parasitic eggs is the main source for toxocariasis and other geohelminth infections of humans. This study aimed to determine the prevalence and associated risk factors for intestinal parasitic infections in dogs and the degree of soil contamination with Toxocara eggs in Kandy and Gampaha districts in Sri Lanka. Methods: A total of 188 fecal samples from both stray and domestic owned dogs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…This result was slightly different from a previous report where contamination was detected in 12.0% of the soil samples collected from schools in Sakon Nakhon Province [6] in the northeastern region and in 18.3% of the soil samples in Nakhon Si Thammarat Province [7] in the southern region. Our results revealed higher contamination rates than those in Iran (13.0%) [18], Sri Lanka (12.0%) [19], Poland (1.6%) [20], and Brazil (0.5%-8.3%) [12,21], but lower than those reported in Iran (18.0%-47.5%) [9,22,23], Malaysia (24%) [2], Poland (20.7%) [17], Russia (23.3%) [24], Brazil (27.3%-38.4%) [25,26], Greece (17.1%) [27], Peninsula (26.6%) [28], Portugal (63.2%) [29], Serbia (22.0%-26.0%) [30], Turkey (19.4%) [31], and Germany (23.2%) [32]. Toxocara spp.…”
Section: Discussioncontrasting
confidence: 57%
“…This result was slightly different from a previous report where contamination was detected in 12.0% of the soil samples collected from schools in Sakon Nakhon Province [6] in the northeastern region and in 18.3% of the soil samples in Nakhon Si Thammarat Province [7] in the southern region. Our results revealed higher contamination rates than those in Iran (13.0%) [18], Sri Lanka (12.0%) [19], Poland (1.6%) [20], and Brazil (0.5%-8.3%) [12,21], but lower than those reported in Iran (18.0%-47.5%) [9,22,23], Malaysia (24%) [2], Poland (20.7%) [17], Russia (23.3%) [24], Brazil (27.3%-38.4%) [25,26], Greece (17.1%) [27], Peninsula (26.6%) [28], Portugal (63.2%) [29], Serbia (22.0%-26.0%) [30], Turkey (19.4%) [31], and Germany (23.2%) [32]. Toxocara spp.…”
Section: Discussioncontrasting
confidence: 57%
“…A considerable prevalence of canine toxocariasis has been reported in Cebu, Philippines, where a study detected T. canis eggs in 23 out of 200 (11.5%) owned and sheltered dogs ( Urgel et al, 2019 ). A recent study from Sri Lanka reported that Toxocara eggs were found in 4.5% of collected soil samples and 17% of fecal samples collected from stray dogs ( Galgamuwa et al, 2020 ). The seroprevalence rate of human toxocariasis was even higher among suspected cases of visceral larva migrans (50%) and ocular toxocariasis (62%), particularly in children below the age of 14 years ( Iddawela et al, 2017a ; Iddawela et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%